Improving the interaction between large and small industrial enterprises: the theoretical aspect (Путеводитель предпринимателя, 2020)
The article describes the concepts that characterize the current state and forms of interaction of large and small business organizations in the Russian practice, identify opportunities to improve such cooperation.